The Influence of Transformational Leadership and Managerial Competence of Madrasah Principle on the Quality of Madrasah Education at Purwakarta - Sayuti, Ahmad; Qomaruzzaman, Bambang; Surya Siregar, Hariman; Imanuddin Effendi, Dudy (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study aims to analyze the influence of transformational leadership and the managerial competence of head of madrasah on the quality of madrasah education in Purwakarta Regency. The research is grounded in the understanding that the quality of madrasah education largely depends on the effectiveness of leadership and the capacity of madrasah heads to manage institutional resources professionally. An explanatory quantitative approach was employed, using the Structural Equation Modeling (SEM) method based on Partial Least Squares (SmartPLS). The study involved madrasah heads, teachers, and education personnel as the research population, with a sample of 80 respondents. Data were collected using a five-point Likert scale questionnaire that had undergone validity and reliability testing. The findings show that managerial competence significantly and dominantly affects the quality of madrasahs (β = 0.489) and positively influences transformational leadership (β = 0.236). Conversely, transformational leadership demonstrates a weak direct effect on madrasah quality (β = 0.066) and does not function as a significant mediating variable. Theoretically, these results indicate that improving the quality of madrasah is more effective when emphasizing the strengthening of managerial competencies, which should be integrated with the values of Islamic transformational leadership. Overall, this study contributes to the development of leadership theories and practices in Islamic education by highlighting the importance of strategic management capabilities supported by spiritual and value-based leadership.